(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to perform an acid wear properties review (pH, entitlement and buffering effect) of diets that can influence dental and restorative aging. Methodology: Manuscripts from the Pubmed database were collected. The search terms were: “Dental erosion”, “Erosion”, “Food habits”, “acidity”, “tooth enamel solubility”, “carbonated drinks”, “hydroxyapatite” and “alcoholic beverage consumption” between the years of 1995 and 2020. Result: 755 manuscripts were initially obtained, but after analyzing the inclusion and exclusion criteria, 15 manuscripts were selected at the end. After analyzing the 15 manuscripts included in the literature review, the results of the study showed that most of the diets evaluated had a pH lower than 5.5, except for coffee and mineral water. The soft drinks and Kombucha had lower pH values and therefore more corrosive potential. Conclusion: Based on the results of this study, it may be concluded that most of the diets evaluated present a corrosive potential for dental structure and restorative materials.